2023
DOI: 10.3390/nu15153448
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiproliferative Apoptosis Induction and Cell Cycle Arrest Potential of Saudi Sidr Honey against Colorectal Cancer

Abstract: A range of natural products have been extensively studied for their chemopreventive potential for cancer, including those that inhibit growth and induce apoptosis. Sidr honey derived from the Ziziphus or Lote tree (Ziziphus spina-christi, Ziziphus lotus, or Ziziphus jujuba) is used in a wide range of traditional medicine practices. In the current study, the Saudi Sidr honey was analyzed by means of a GC–MS chromatogram and investigated for its antiproliferative effects on colorectal cancer cells (HCT-116), bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…They also reported a strong antioxidant activity against DPPH (IC50 0.670 mg/mL), ABTS (IC50 3.554 mg/mL), and β-carotene (IC50 > 5 mg/mL) [ 104 ]. Sidr honey has shown a notable cytotoxic effect in a dose-dependent manner against three cancer cell lines including lung (A549), breast (MCF-7), and colon (HCT-116), with respective IC50 values of 5.203%, 6.02%, and 7.257% [ 105 ]. A study also reported the presence of bioactive compounds such as phenolic compounds, vitamin C, total phenolic contents (TPCs), radical scavenging activity (RSA), and sugars of five honey samples (Talh, Athel, Sidr, Spring flower, and Langnese) from the Hail region (Saudi Arabia) using HPLC-RID and DAD [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a strong antioxidant activity against DPPH (IC50 0.670 mg/mL), ABTS (IC50 3.554 mg/mL), and β-carotene (IC50 > 5 mg/mL) [ 104 ]. Sidr honey has shown a notable cytotoxic effect in a dose-dependent manner against three cancer cell lines including lung (A549), breast (MCF-7), and colon (HCT-116), with respective IC50 values of 5.203%, 6.02%, and 7.257% [ 105 ]. A study also reported the presence of bioactive compounds such as phenolic compounds, vitamin C, total phenolic contents (TPCs), radical scavenging activity (RSA), and sugars of five honey samples (Talh, Athel, Sidr, Spring flower, and Langnese) from the Hail region (Saudi Arabia) using HPLC-RID and DAD [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some in vivo studies have been performed on mice/rats, where tumors were either induced or transplanted. [16][17][18] Honey plays a role in various stages of cancer, including initiation, growth, and advancement. Its anticancer properties are typically linked to several mechanisms.…”
Section: 12mentioning
confidence: 99%
“…Yemeni Sidr honey (YSH) is a particular example of a natural product with distinct anti-cancer effects [12,13], and it has similar properties to some other types of honey, including Tualang honey and Manuka honey [14][15][16]. Tualang honey is produced in Southeast Asia by the giant honey bee Apis dorsata from multiple flora, and Manuka honey is a monofloral honey produced by honeybees from the nectar of the Manuka honey bush (Leptospermum scoparium) throughout New Zealand and Australia [5,17].…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of Yemeni honey is Sidr honey, produced by bees from the nectar of the Ziziphus spina-christi tree from the remote Dawan and Gerdan areas of Hadramout and Shabwa [9,11]. The result is one of the most prized and expensive monofloral honeys available [12,13]. In other locations, Sidr honey is harvested from bees that derive the nectars of the jujube tree (also known as Christ's Thorn Jujube) and is utilized for a variety of medicinal purposes [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation